Interleaved Hybrid Converter with Simultaneous DC and AC Outputs for DC Microgrid Applications - Bussa V.K.; Ahmad A.; Singh R.K.; Mahanty R. (My University, 2025)
This paper proposes an interleaved hybrid converter (IHC) with simultaneous dc and ac outputs for dc microgrid applications. The IHC is realized by interleaving two conventional boost converters and replacing the active switch of lower boost converter by an H-bridge voltage source inverter. This arrangement enables the proposed IHC to operate at the condition where the sum of duty ratio (D ) and modulation index (M) can be more than or equal to one, i.e., D + M 1, unlike the conventional hybrid converters. The proposed IHC is capable of giving dc with high voltage gain and improved ac with reduced harmonic distortion. Due to interleaving nature of the IHC, input current is shared between the power converters and thus enables the use of low current rated switching devices and lower values of inductors. This results in reduced power losses and increased efficiency as compared to the conventional hybrid converters. The IHC also has inherent shoot-through protection capability, better electromagnetic interference immunity, and reliability. A modified unipolar sinusoidal pulse width modulation technique is used to control the power flow of the IHC. Detailed mathematical modeling of the proposed IHC is carried out and its steady-state behavior is validated through experimental results on a 500 W laboratory prototype. © 1972-2012 IEEE.